Prediction of Dangerous Areas for Food Desertification in Gyeonggi Province - Kim, Sehyoung; Cheon, Seyeon; Park, Jae Hyeong; Park, Seongwoo; Kim, Haesung; Kang, Juyoung (International Conference on ICT Convergence, 2022)
Food desertification refers to a phenomenon in which it has become difficult to obtain fresh food including vegetables in the community. In the past, research on food desertification risk areas has not been conducted properly in Korea. Since the phenomenon of food desertification is accelerating due to the increase of single-person households and the elderly, research on food desertification is needed to solve and prevent food desertification. In addition, so far, food desertification studies have been conducted only to the extent of deriving case studies and food desertification areas, but no research has been conducted to predict this. In this study, food desertification risk areas were derived, and a predictive model was produced to prevent this.
Keywords: Case-studies; Dangerous area; Desertification risk; Food desertification; Fresh food; Machine-learning; Predictive models; Prevention of food desertification; Risk areas; Big Data; Data Analysis; Food Desertification; Machine Learning; Prevention of food desertification